2011
DOI: 10.1590/s1679-45082011ao1848
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dental care associated with laser therapy on oral mucositis during allogeneic hematopoietic cell transplant: retrospective study

Abstract: Dental care associated with laser therapy reduces the extension and severity of oral mucositis in patients with allogeneic hematopoietic transplant. Further studies are necessary to clarify the isolate efficacy of laser therapy in these conditions, mainly regarding the influence of reduced oral mucositis on the graft versus host disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
3
0
3
Order By: Relevance
“…Another study showed that the use of laser therapy and dental care reduced the morbidity of oral mucositis, also reducing the costs of hospitalization. (204)…”
Section: Low-intensity Laser Therapymentioning
confidence: 99%
“…Another study showed that the use of laser therapy and dental care reduced the morbidity of oral mucositis, also reducing the costs of hospitalization. (204)…”
Section: Low-intensity Laser Therapymentioning
confidence: 99%
“…( 1 , 2 , 8 ) These lesions usually lead to a significant decrease in quality of life, since they can prolong hospital stay, affect the nutritional status of the patient, increase the risk of infections, and increase the prescription of opioids. ( 9 - 11 )…”
Section: Introductionmentioning
confidence: 99%
“…Desta maneira, faz-se necessário lançar mão de ferramentas que previnam sobre a MO. Dentre elas, destacam-se os cuidados básicos de higiene oral, que incluem a realização de uma boa escovação com uso de dentifrícios uoretados, bem como o uso do o ou ta dental, de forma a reduzir a ação da ora bacteriana patogênica existente na cavidade oral (23,32,36) ; bochechos com dexametasona elixir, devido ao seu efeito anti-in amatório (28) ; aplicação de laser de baixa potência (LBP) por suas propriedades analgésica, anti-in amatória e de estímulo regenerativo (29,32,(37)(38) ; administração de analgésicos sistêmicos (32) e agentes naturais, como o mel (35) .…”
Section: Mucosite Oralunclassified